Tailored wet-chemical synthesis of spheroidal AgNps: Exploring optical, morphological, and biological correlations through experimental parameter variation - Santos, João Antonio Oliveira [UNESP]; Martin, Cibely da Silva [UNESP]; Fulindi, Rafael Bianchini [UNESP]; da Costa, Paulo Inácio [UNESP]; Pires, Ana Maria [UNESP]; Cebim, Marco Aurélio [UNESP]; Lima, Sergio Antonio Marques [UNESP] (Elsevier, 2024)
Spherical silver nanoparticles (AgNps) show high scientific, economic, and biotechnological interest related to their photonic properties associated to the fascinating plasmonic absorption and antimicrobial activity, however, their synthesis using wet-chemical methods remains a challenge, in terms of control, repeatability, and reproducibility. Herein, we investigated two adapted strategies to produce water-suspended spheroidal and homogeneous AgNps by using sodium citrate (CT) and ascorbic acid (AA) as stabilizing and reducing agents, respectively. We also show the impact of experimental parameters such as reactional time, temperature, and precursor concentration, as well as their order/method of addition on the morphology and optical properties of AgNps that were intrinsically correlated through extinction spectra and transmission electron microscopy (TEM), additionally the activity of prepared AgNPs colloidal suspensions were tested against Staphylococcus aureus bacterium. The most controllable synthesis condition was achieved by methodology in which the silver precursor is added dropwise (one drop per second) to a solution at 70 °C containing CT and AA keeping the stirring for 20 min. The proposed methodology presented a high repeatability of the syntheses generating AgNps with regular size and shape (between 22 and 30 nm), being stable in water up to one year with slight changes in its plasmonic and morphological properties. A scale-up trial was also performed and the dropwise methodology allowed the obtention of spheroidal-AgNps suspensions five times more concentrated with the same morphological and optical control, which saves time and energy in the synthesis process. The AgNPs demonstrated a good antibacterial potential when the samples are freshly prepared, losing their activity as the samples age.
Keywords: Ascorbic acid; Plasmonic band; Repeatability; Spherical AgNps; Staphylococcus aureus; Wet-chemical method